Humoral and cellular immune response to AZD1222 /Covishield and BV152/Covaxin COVID-19 vaccines among adults in India - Anuradha S. Tripathy; Dharmendra Singh; Diptee Trimbake; Sukeshani Salwe; Srikanth Tripathy; Arjun Kakrani; Priyanka Jali; Hanmant Chavan; Pragya Yadav; Rima Sahay; Prakash Sarje; Prasad Babar; et al. (Taylor & Francis Group, 2024)
Several COVID-19 vaccines were developed using different approaches to prevent both symptomatic COVID-19 cases and fatalities. The adults were vaccinated with two doses of AZD1222/Covishield (n = 77) [manufactured by Serum Institute of India Pvt Ltd] vaccine and BV152/Covaxin (n = 99) [manufactured by Bharat Biotech] vaccine. They were assessed for immune response at pre-vaccination, 1 month post first and 6 months post second dose for anti-SARS-CoV-2 IgG antibody, surrogate neutralizing antibody (NAbs), immune phenotypes, antigen specific NK, B and T cell response, their effector functionality by ELISPOT and plasma cytokine profile. Both vaccines elicited enhanced IgG antibody and Nab levels compared to the baseline. BV152/Covaxin, the whole virus inactivated vaccine exhibited higher IgG (70% vs 100%), Nab (90% vs 100%), and robust T cell (31% vs 96%) responses at 6 months post second dose compared to 1 month post first dose justifying the utility of the second dose. Detection of SARS-CoV-2 WV and S1 specific CD4+ central T cell memory response in AZD1222/Covishield vaccinee at 6 months post second dose and higher CD4+ and CD8+ naïve and central memory T cell response in BV152/Covaxin vaccinee at 1 month post first dose indicated the involvement of memory T cells. Persistent IgG and NAb responses along with IgG+B and IgG+memory B cells in AZD1222/Covishield recipients at 6 months post second dose indicated sustained immune memory response. Continued heightened IFN-γ secreting T cell response (ELISPOT) displayed by both the vaccine platforms could serve as a co correlate of protection, further to evaluation in follow up studies. Overall, our data suggest that coordinated functions of humoral and cellular branches of adaptive immunity may pave ways toward protective immunity against COVID-19.